Análise das auditorias operacionais do tribunal de Contas do Estado de Minas Gerais: uma avaliação à luz da Teoria Neoinstitucional - Fonseca, Marina Moraes Raso Sardinha (2020)
The New Public Management paradigm still influences the Brazilian public administration, especially regarding the permanence of the search for results, an aspect related to the development of the performance audit, whose proposal refers to the investigation of efficiency, economy, effectiveness, effectiveness of governmental activities, programs and institutions. Neo Institutional theory, on the other hand, highlights how institutions constantly need to reaffirm their legitimacy and the justification for their existence, which is often sought through the adoption of accepted and widespread practices within the scope of their organizational field, regardless of proof of their effectiveness. In this sense, it was analyzed the hypothesis that the performance of operational audits by the TCE-MG gives it institutional legitimacy in its sphere of operation, once it results from isomorphism in relation to practices adopted by Higher Audit Institutions considered references in this context, especially the TCU. Thus, from the identification of how operational audits have been carried out, especially at the TCE-MG, it was found that their performance in this body began due to mimetic and coercive isomorphism, especially in relation to the TCU, and has been institutionalized as a recognized type of government audit. Therefore, important audits of this nature have been produced, which have identified relevant deficiencies in public policies in the State of Minas Gerais and its municipalities. However, it was found that, in many respects, given the historical trajectory of the institution, which during most of its existence performed its audits from the perspective of regularity audits, the development of operational audits was, at least in part, influenced by this logic of action, implying similarities between these and regulatory audits, such as: the predominance of issues related to processes, meta-evaluation and the achievement of goals to the detriment of studies on impact and cost-benefit or costeffectiveness; conducting audits from a predominant perspective of law enforcement; the inclusion of the processes for monitoring operational audits on the analysis agenda under the same rite as the other audit processes, not considering the urgency of their timeliness for their effectiveness. Thus, the commitment to achieve the full scope of the agency's operational audits proposal was identified, mainly due to the recommendations produced in them and to the large time lag in the processing between the preparation of its report and the monitoring of compliance with the action plan, they are based on a different context from the one observed when the adoption of the measures provided for in the document is verified, often causing the effective contribution that the audit could generate in public management to be impaired. Therefore, considering the peculiarity of the operational audits, an eventual internal normative provision of the TCE-MG in order to stipulate a maximum period for the conclusion of these analyzes could contribute to the speed of its procedures, thus enabling the monitoring of the fulfillment of the commitments signed in the action plan in a period of time closer to the context observed at the time of the audit, ensuring greater suitability of its recommendations and determinations and greater effectiveness in its contributions to public management.